What's on your hard drive?. - O'Hanlon, Charlene (New York ACM, 2005)
One of the most interesting things about WOYHD is seeing how often certain tools appear under either the "love" or "hate" categories. In fact, over the past year we've developed a keen sense of which tools our readers love most and which they loathe most. It's not that our data says anything about the overall popularity of any one product. A product that receives a large number of "hates" actually could be the most popular tool on the market. We invite you to add to the love and hate tallies at www.acmqueue.com.
Keywords: General Literature; Miscellaneous